A modified spin-casting approach for scalable preparation of ultra-thick reduced graphene oxide films with high thermal conductivity. (1st March 2022) - Liu, Dapeng; Fu, Huili; Yang, Tingting; Wang, Wenjing; Zhao, Jingna; Wu, Kunjie; Wu, Cao; Yong, Zhenzhong; Zhang, Yongyi
Abstract: With the fast development of high-power electronic devices in recent years, the demand for high-performance thermal dissipation films with high thermal conductivity and large thickness has dramatically increased. Graphene has shown great potential in thermal management due to its extremely high thermal conductivity. However, it remains a significant challenge to achieve high thermal conductivity in thick graphene films (≥100 μ m). Herein, a scalable strategy combining a modified layer-by-layer 'spin-casting' solution deposition method and multi-step annealing post treatment was adopted for preparing ultra-thick, highly thermal conductive graphene films. The properties of the graphene films were characterized by SEM, XRD, Raman, and XPS, exhibiting excellent graphitic crystallinity, well aligned and dense packing assembly structure. These nearly ideal structural features endow the graphene films with high in-plane thermal conductivity of 1265 ± 46 W m −1 K −1 at a large thickness of 100 μ m. The ultra-thick graphene films show superior thermal dissipation performance as compared with traditional Cu/Al foil, demonstrating their great potential in the field of highly-efficient heat spreader films for the next generation of high-power devices.